2021
DOI: 10.1111/jfpp.16040
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phenolics and antioxidant capacities in fruit tissues of mandarin cultivars Kinnow and W. Murcott with relation to fruit development

Abstract: Citrus fruits are known for their valuable phytochemicals such as flavonoids, carotenoids, and limonoids. The Punjab province of northwestern India is bestowed with a diversity of citrus cultivars that can be successfully grown. Citrus acreage in region is 60,980 ha, with cultivar Kinnow (Citrus nobilis Lour × Citrus deliciosa Tenora) mandarin comprising 55,470 ha and covering 91% of the total area under citrus fruits (Anonymous, 2020). Similarly, cultivar W. Murcott (Citrus reticulate Blanco × Citrus sinensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Simpson & Egyankor [63] reported that the highest pectin content 4.10% was present at fully mature stage of Grape fruit. Moreover, the pectin content increased in case of Kinnow and Orange fruit, which might be attributed to presence of pectin degrading enzyme inhibitors [64,65]. Similar findings are expected in case of Ttangerine fruits [66].…”
Section: Pectin Contentsupporting
confidence: 77%
See 1 more Smart Citation
“…Simpson & Egyankor [63] reported that the highest pectin content 4.10% was present at fully mature stage of Grape fruit. Moreover, the pectin content increased in case of Kinnow and Orange fruit, which might be attributed to presence of pectin degrading enzyme inhibitors [64,65]. Similar findings are expected in case of Ttangerine fruits [66].…”
Section: Pectin Contentsupporting
confidence: 77%
“…Naringin content decreased in most of the citrus fruits owing to its hydrolysis by naringinase [71][72][73][74] however, presence of inhibitors might result in its increase, as in case of bitter Orange [75]. --0.18 Grape fruit (mg/100 g FW) [68] 12102 -2195 Tangerine (mg/l) [71] 181 154 140 Kinnow (mg/g DW) [65] 0.68 1.21 0.54 Mandarin (µg/g) [73] 15.31 3.03 4.31 Bitter Orange (%) [58] 13.29 15.03 19.29 Pamelo (µg/ml) [54] 40.27 7.56 0.53 Chinotto (mg/l) [74] 19.95 -6.08 Clementine (mg/g DW) [69] --0.08…”
Section: Naringin Contentmentioning
confidence: 99%
“…Sainampueng. Singh et al reported that W. Murcott pulp contained higher mean total phenol content than Kinnow pulp (1547 versus. 1279 mg GAE/100 g DW).…”
Section: Resultsmentioning
confidence: 99%
“…Costanzo et al 9 reported lower DPPH activity (21.10%) in mandarin fruits. Singh et al 2 used DPPH assay in two mandarin cultivars and reported DPPH activity from 26.54 to 85.46% during different fruit developmental stages. China Xu et al 48 investigated antioxidant activity of different groups of mandarins (diverse species) and found DPPH value between 23.69 and 61.62%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation